Kinetics of Osmotic Responces ofNucieated Cells of Mice Bone Marrow and Human Cord Blood at the Stage of Penetrating Cryoprotectant Removal - Kholodnyy, V. S.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2002)
The behaviour of nucleated cells of mice bone marrow and human cord blood during their transfer out of DMSO, 1,2-propane diol (PD) and glycerol solutions has been studied. Using modified model of Kedem-Katchalsky the penetration coefficients of plasmatic membranes of cells at the stage of cryoprotectant removal out of them were determined.